2016
DOI: 10.1139/cjpp-2015-0266
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic value of melatonin post-treatment on CCl4-induced fibrotic rat liver

Abstract: Melatonin is known for being beneficial in targeting liver diseases. This study aimed to investigate whether melatonin post-treatment is capable of rat carbon tetrachloride (CCl)-induced liver fibrosis reduction. Thirty-two male Sprague-Dawley rats were divided into 4 groups: normal; fibrosis with CCl injection (1 mL/kg) twice weekly for 8 weeks; phosphate-buffered saline (PBS); and melatonin (20 mg/kg) for a further 4 weeks on cessation of CCl. At the beginning of week 13, liver tissue samples were used for h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 52 publications
0
39
0
Order By: Relevance
“…In a study, it was demonstrated that melatonin attenuated CCl 4 -induced liver fibrosis through preventing necroptosis-associated inflammatory signaling. Melatonin reduced hepatic hydroxyproline content, hepatocellular damage, and transforming growth factor β1 and α-smooth muscle actin expression [145,146]. Moreover, melatonin significantly attenuated RIP1 expression, RIP1 and RIP3 necrosome complex formation, and mixed lineage kinase domain-like protein level in the liver [145].…”
Section: Protective Effects Of Melatonin On Liver Fibrosismentioning
confidence: 99%
“…In a study, it was demonstrated that melatonin attenuated CCl 4 -induced liver fibrosis through preventing necroptosis-associated inflammatory signaling. Melatonin reduced hepatic hydroxyproline content, hepatocellular damage, and transforming growth factor β1 and α-smooth muscle actin expression [145,146]. Moreover, melatonin significantly attenuated RIP1 expression, RIP1 and RIP3 necrosome complex formation, and mixed lineage kinase domain-like protein level in the liver [145].…”
Section: Protective Effects Of Melatonin On Liver Fibrosismentioning
confidence: 99%
“…Melatonin is a secretory product of the pineal gland and gastrointestinal tract during night and daytime, respectively (Margheri et al, ). Melatonin is responsible for a variety of physiological functions (Mortezaee, Khanlarkhani, Sabbaghziarani et al, ; Mortezaee, Sabbaghziarani et al, ), including antioxidant (Mortezaee & Khanlarkhani, ; Mortezaee et al, ; Mortezaee, Khanlarkhani, Beyer, & Zendedel, ), anti‐apoptotic (Mortezaee, Majidpoor, Daneshi, Abouzaripour, & Abdi, ), and pro‐apoptotic (Lin et al, ) activities. Melatonin is the only known chronobotic hormone for regulation of neoplastic cell growth (Blask, Sauer, & Dauchy, ).…”
Section: Introductionmentioning
confidence: 99%
“…CCl 4 has been used as the most common experimental model of chemically induced liver fibrosis (Ogeturk et al, ) and cirrhosis (Oliveira‐Junior et al, ) in rodents causing damages resemble those seen in human subjects (Mortezaee, Sabbaghziarani, et al, ). Metabolization of CCl 4 produces • CCl 3 that reacts with O 2 to form CCl 3 normalO2 (Shaker et al, ).…”
Section: The Role Of Oxidative Stress In Liver Fibrosis and Cirrhosismentioning
confidence: 99%